Molecular cloning of genes involved with expression of A-band lipopolysaccharide, an antigenically conserved form, in Pseudomonas aeruginosa. - Lightfoot, J (1991)
Most strains of Pseudomonas aeruginosa can express two chemically and immunologically distinct types of lipopolysaccharide (LPS), an antigenically conserved form called A band and the serotype-specific form called B band. To study the molecular controls regulating expression of the A-band LPS antigen, we have cloned the genes involved with A-band LPS expression. Strain AK1401, a phage-resistant mutant of PAO1 which was shown previously to produce only A-band LPS and not the O-antigen-containing B-band LPS, was mutagenized by using ethyl methanesulfonate to generate an A-band-deficient mutant called rd7513. A cosmid clone bank of P. aeruginosa PAO1 whole genomic DNA was constructed in Escherichia coli. The gene bank was mobilized en masse into strain rd7513, and detection of complementation of synthesis of A band was done by screening transconjugants in a colony immunoblot assay with the A-band-specific monoclonal antibody N1F10. One recombinant cosmid, pFV3, complemented synthesis of A-band polysaccharide in rd7513. Silver-stained polyacrylamide gel and Western immunoblot analyses of LPS extracted from the transconjugant rd7513(pFV3) showed that the A band produced had a higher molecular weight than the A band of AK1401. Analysis of the plasmid pFV3 showed that it contained a chromosomal insert of 27 kb. Two subclones of pFV3, namely, pFV35 and pFV36, containing chromosomal inserts of 5.3 and 4.2 kb, respectively, also complemented A-band expression in rd7513. The LPS banding profile of rd7513(pFV35) was similar to that of AK1401, while the LPS profile of rd7513(pFV36) more closely resembled that of rd7513(pFV3). pFV3 complemented A-band expression in five of the six P. aeruginosa O serotypes which lack A band as well as in rough strain AK44 but failed to complement A-band expression in core mutants AK1012 and AK1282, suggesting that pFV3 contains genes for A-band expression and that synthesis of a complete core region in isogenic mutant strains is required for A-band synthesis.